Advances in Cryogenic Engineering Materials 1986
DOI: 10.1007/978-1-4613-9871-4_48
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Mechanical Properties of Al-Cu-Li-Zr Alloy 2090

Abstract: The mechanical properties of aluminum-lithium alloy 2090-T8E41 were evaluated at 298 K, 77 K, and 4 K. Previously reported tensile and fracture toughness properties at room tem.,lerature were confirmed. This alloy exhibits substantially improved properties at cryogenic temperatures; the strength, elongation, fracture toughness and fatigue crack growth resistance all improve simultaneously as the testing temperature decreases. This alloy has cryogenic properties superior to those of aluminum alloys currently us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 1 publication
1
24
1
Order By: Relevance
“…However, as illustrated by figure 2, decreasing the temperature did not alter the fracture mode or morphology [1]. More recently, Dorward [2] has suggested that the improvement in the fracture toughness of 2090-TS alloy at low temperature is due to increased short-transverse delamination (splitting in the plane of the plate).…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…However, as illustrated by figure 2, decreasing the temperature did not alter the fracture mode or morphology [1]. More recently, Dorward [2] has suggested that the improvement in the fracture toughness of 2090-TS alloy at low temperature is due to increased short-transverse delamination (splitting in the plane of the plate).…”
Section: Introductionmentioning
confidence: 90%
“…In addition, previous work has indicated that at low temperatures aluminum-lithium alloys display improved toughness and an improved strength-toughness relationship in the Land LT directions [1][2][3]. The most extensively studied alloy is alloy 2090-TBl, of nominal composition Al-2.7Cu-2.2Li-0.12Zr in weight 2 percent.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations